1992
DOI: 10.1136/jnnp.55.7.546
|View full text |Cite
|
Sign up to set email alerts
|

Primary intracerebral haemorrhage in the Jyvaskyla region, central Finland, 1985-89: incidence, case fatality rate, and functional outcome.

Abstract: Primary intracerebral haemorrhage in the Jyvaskylai region, Central Finland, 1985-89: incidence, case fatality rate, and functional outcome R Fogelholm, M Nuutila, A-L Vuorela Abstract The age and sex specific incidence rates, the case fatality rates, and the functional outcome of patients with primary intracerebral haemorrhage occurring in a population of 116 000 during a period of four years four months are presented. A total of 158 patients were identified, the diagnosis was confirmed in 78% by CT, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
2
6

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(86 citation statements)
references
References 31 publications
10
68
2
6
Order By: Relevance
“…Surgical treatment was performed after the clotting tests were brought to normal levels. In the literature, the idiopathic intracerebral hemorrhage ratio varies between 6-12% (20,21). In our study we found this ratio to be 12% (8 cases), which is consistent with the literature.…”
Section: Discussionsupporting
confidence: 92%
“…Surgical treatment was performed after the clotting tests were brought to normal levels. In the literature, the idiopathic intracerebral hemorrhage ratio varies between 6-12% (20,21). In our study we found this ratio to be 12% (8 cases), which is consistent with the literature.…”
Section: Discussionsupporting
confidence: 92%
“…Previous surveys, have found that 30-day mortality rates range from 35% in Australia 1) , 44% in the United States 7) , and up to 51% in France 15) , England 3) , and Finland 13) . Surprisingly, a recent study conducted by Inagawa et al 19) in Japan returned a 30-day mortality rate after PICH of only 14%.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in comparison with an equivalent-sized ischemic infarct, in patients with SICH, an intraparenchymal blood leads to an increased inlammation and a greater cell death [26,31]. There is growing evidence that recovery in functions is beter in patients with SICH than in patients with ischemic strokes [6,[32][33][34][35][36][37][38][39][40][41][42]. The recovery process starts in the acute phase and can continue for months in the recovery phase [38,43,44].…”
Section: Rehabilitation and Recoverymentioning
confidence: 99%
“…[2]. SICH accounts for approximately 10-20% of all stroke cases, carries a 30-day mortality of up to 50%, and causes signiicant and persistent disability in survivors [3][4][5][6][7]. Advances in the management of the SICH have resulted an increase in survival, particularly in cases of smaller lesions; however, larger SICH lesions remain a signiicant cause of morbidity and mortality globally [8,9].…”
Section: Introductionmentioning
confidence: 99%